Ephemeral Inscriptions: Graffiti, Gentrification, and the Struggle for Public Space in the Indonesian Metropolis - Bimala Putri; Omar Alieva; Henny Kesuma; Ifah Shandy; Ni Made Nova Indriyani (Enigma Institute, 2025)
The visual landscape of the contemporary city is a contested terrain where cultural expression and economic forces collide. This study investigates the complex relationship between graffiti practices and gentrification in Indonesia, moving beyond a simple resistance-versus-commodity binary to analyze graffiti as a dialectical force in urban transformation. It examines how graffiti functions as a mode of spatial inscription, a carrier of urban affect, and a critical barometer of the struggle for the right to the city in the Global South. This research employed a longitudinal, mixed-methods, comparative case study design, focusing on the Glok district in Jakarta and the Braga district in Bandung (2019-2025). The methodology integrated quantitative spatio-temporal GIS analysis of 1,250 graffiti pieces correlated with economic data, and a systematic content analysis of their form and themes. This was triangulated with deep qualitative data from 24 months of ethnographic fieldwork and 45 semi-structured interviews with artists, residents, and officials. A critical positionality statement reflects on the ethical praxis of the research. The findings reveal a clear trajectory where illicit, text-based graffiti, initially prevalent in peripheral spaces, created a subcultural